Compensation for Cross-Coupled Dynamics of Dual Twisted-String Actuation Systems - Lei Jiang; Yuejuan Li; Marvin H. Cheng (Journal of Control Science and Engineering)
Twisted-string actuation devices have been adopted in various robotic systems due to their advantages of compact size and simple structure. To precisely control the displacement of such devices, a dual-direction actuating mechanism, which provides both extension and contraction of two strings simultaneously, must be implemented. Due to the physical properties of twisted string, the actuator has problems of nonlinear length variation and cross-coupled relationships between two strings. In this study, two controllers (PID-FC and LQR-FC) were synthesized with the consideration of cross-coupling dynamics between the two axes. The experimental results demonstrate the performance of both tracking and synchronization responses of these two types of controllers.